Wind data logger - Siti Hanis, Sidek (2009)
When planning to install a wind turbine, one must predict the power output that will generated by studying the wind speed at the potential location. These projects intend to study the potential for wind turbine installation in UMP. A data logger is developed to measure and record the wind parameter, speed. Wind speed is determined by measuring the number rotation of anemometer within a certain period of time. The parameters obtain by these device will be collected by a microcontroller and transmitted to a personal computer through radio frequency signal. All data be recorded and analysis to decide the potential for wind turbine installation.